2020
DOI: 10.1155/2020/3165958
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis, Characterization, and Expression Profile of the Basic Leucine Zipper Transcription Factor Family in Pineapple

Abstract: This study identified 57 basic leucine zipper (bZIP) genes from the pineapple genome, and the analysis of these bZIP genes was focused on the evolution and divergence after multiple duplication events in relation to the pineapple genome fusion. According to bioinformatics analysis of a phylogenetic tree, the bZIP gene family was divided into 11 subgroups in pineapple, Arabidopsis, and rice; gene structure and conserved motif analyses showed that bZIP genes within the same subgroup shared similar intron-exon or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 69 publications
1
9
0
Order By: Relevance
“…RsbZIP031 and RsbZIP059 in radish were significantly downregulated under high temperature and salt stress, respectively [27]. In pineapple root tissues, AcobZIP24 has a significant response to salt, drought, cold, and heat stresses at 24 and 48 h [28]. These examples illustrate the response of bZIP TFs in plants to various abiotic stresses.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…RsbZIP031 and RsbZIP059 in radish were significantly downregulated under high temperature and salt stress, respectively [27]. In pineapple root tissues, AcobZIP24 has a significant response to salt, drought, cold, and heat stresses at 24 and 48 h [28]. These examples illustrate the response of bZIP TFs in plants to various abiotic stresses.…”
Section: Introductionmentioning
confidence: 87%
“…Research into the bZIP family in different species will bring new insights into its evolution and function. Previous studies have shown that the bZIP TF family is involved in the regulation of genes involved in organ and tissue differentiation [15][16][17][18], seed storage [19,20], pathogen defence [21], the unfolded protein response [22][23][24], photomorphogenesis and light signal regulation [25,26], hormone and sugar signaling processes [27,28], and responses to abiotic stress [3,29,30]. Different subfamilies regulate different biological processes.…”
Section: Introductionmentioning
confidence: 99%
“…The basic leucine zipper (bZIP) family is one of the most extensive and varied families of transcription factor (TF) genes in plants ( Liu et al., 2014 ). Regulating numerous biological processes, including plant development, senescence, light signaling, pathogen defense, and reactions to diverse environmental stimuli, depend on ( Van Leene et al., 2016 ; Liu et al., 2020a ). bZIP TFs are characterized by a conserved bZIP domain, spanning 40–80 amino acids ( Castro et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, a large number of bZIP transcription factors have been identified in almost all eukaryotes. There are 57, 77, 62, 96, 85, 87, 89, 262, 92, 89, 178, 103, 65, 69, 125, 64, 55, 114 bZIP transcription factors been found in Ananas comosus , Arabidopsis thaliana , Citrullus lanatus , Fagopyum talaricum, Gossypium raimondii, Gossypium arboreum, Oryza sativa , Glycine max , Sorghum bicolor , Hordeum vulgare L, Panicum virgatum L, Olea europaea L, Solanum tuberosum L., Solanum lycopersicum , Zea mays , Cucumis sativus , Vitis vinifera and Malus domestica , respectively ( Corrêa et al, 2008 ; Nijhawan et al, 2008 ; Wang et al, 2011 ; Wei et al, 2012 ; Baloglu et al, 2014 ; Liu J. Y. et al, 2014 ; Li et al, 2015 ; Pourabed et al, 2015 ; Li et al, 2016 ; Zhang et al, 2018 ; Liu M. et al, 2019 ; Yang W. et al, 2019 ; Azeem et al, 2020 ; Liu et al, 2020 ; Rong et al, 2020 ; Wang et al, 2020 ; Zhao et al, 2020 ). Only 25, 21, and 21 bZIP transcription factors were found in yeast, nematode, and fruit fly, respectively ( Riechmann et al, 2000 ).…”
Section: Distribution and Classification Of Bzip Transcription Factormentioning
confidence: 99%
“…Hence, the classification of bZIP transcription factors has become more and more sophisticated. Due to the advancement of bioinformatics, there are increasing researches provide preliminary analyses on globally identifying bZIP members from the fresh released genomic database of many plants, such as potato, switchgrass, olive, pineapple, cotton, watermelon, and tartaty buckwheat, laying the foundation for subsequent research ( Yang W. et al, 2019 ; Liu M. et al, 2019 ; Azeem et al, 2020 ; Liu et al, 2020 ; Rong et al, 2020 ; Wang et al, 2020 ; Zhao et al, 2020 ). Recent years, there are increasing reports on regulation mechanism of various bZIPs on different stress responses ( Liu et al, 2012 ; Ji et al, 2013 ; Hwang et al, 2014 ; van Leene et al, 2016 ; Tsugama et al, 2016 ; Zhang C. Y. et al, 2017 ; Zhang L. N. et al, 2017 ; Wang et al, 2019 ).…”
Section: Distribution and Classification Of Bzip Transcription Factormentioning
confidence: 99%